Perinatal outcomes in pregnant women with hypertensive syndromes: an integrative review - Cassiano, Alexandra do Nascimento (2020)
Objective: to identify in the literature the perinatal outcomes in pregnant women with hypertensive syndromes. Method: it is an integrative review with collection of publications indexed in LILACS¸ PUBMED, SCOPUS and WEB OF SCIENCE, during January 2017. The descriptors used were: pregnancy-induced hypertension, perinatal care and neonatology. Results: the most frequent perinatal outcomes were: perinatal mortality, prematurity, low APGAR in the 1st and 5th minute of life, newborns small for gestational age, admission to the intensive care unit, intrauterine growth restriction and cesarean delivery. Among the pathologies investigated, pre-eclampsia stood out (80.6%) and 3% of the articles addressed severe pre-eclampsia. Conclusions: the realization of investigations that analyze the exposure of the fetus / neonate to the maternal condition of severe pre-eclampsia and chronic hypertension overlapped by pre-eclampsia, constitutes knowledge gaps.